Fast recursive algorithm for implementation of MIMO ZF-SIC detection - Zuo-liang YIN; Xing-peng MAO; Qin-yu ZHANG; Nai-tong ZHANG (Tongxin xuebao)
To reduce the complexity of the zero-forcing(ZF)detection with successive interference cancellation(SIC)in a Vertical Bell Labs layered space-time(V-BLAST)systems,a computationally efficient recursive algorithm was proposed.A fast implementation of the proposed algorithm was developed and its complexity was analyzed in detail.Theoretical analysis and simulations demonstrate significant advantages of the proposed algorithm over the fast recursive algorithm (FRA)on complexity,practicability and storage requirements.Moreover,its performance on symbol error rate(SER)is close to optimal under practical conditions.These advantages make the proposed algorithm more efficient and practical.